Improving the Information Availability and Accessibility of Antenatal Measurements to Ensure Safe Delivery: A Research-Based Policy Recommendation to Reduce Neonatal Mortality in Indonesia - Anggraini D; Abdollahian M; Marion K; Asmu'i; Meilania GT; Annisa AS (Dove Medical Press, 2020)
Dewi Anggraini,1 Mali Abdollahian,2 Kaye Marion,2 Asmu’i,3 Gusti Tasya Meilania,1 Auliya Syifa Annisa1 1Study Program of Statistics, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat University, Banjarbaru, South Kalimantan, Indonesia; 2School of Science, College of Science, Engineering, and Health, RMIT University, Melbourne, VIC, Australia; 3Study Program of Public Administration, Faculty of Social and Political Sciences, Lambung Mangkurat University, Banjarmasin, South Kalimantan, IndonesiaCorrespondence: Dewi AnggrainiStudy Program of Statistics, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat University, Ahmad Yani Street, Km. 36, Banjarbaru 70714, South Kalimantan, IndonesiaTel/ Fax +62 511 4773112Email dewi.anggraini@ulm.ac.idPurpose: Assessing the risks and preventable causes of maternal and neonatal mortality requires the availability of good-quality antenatal information. In Indonesia, however, access to reliable information on pregnancy-related results remains challenging. This research has proposed a research-based policy recommendation to improve availability and accessibility to vital information on antenatal examinations.Patients and Methods: Descriptive statistics were used to characterize midwives’ capabilities in routinely gathering and recording antenatal information during pregnancy. The investigation was carried out among 19 midwives in South Kalimantan, Indonesia, from April 2016 to October 2017. Antenatal data on 4946 women (retrospective study) and 381 women (prospective study) have been accessed through a scientific and technical training program.Results: To date, lack of timely access to antenatal information has hampered the process of reducing neonatal mortality in Indonesia. The post-training statistical analysis showed that the training has significantly improved midwives’ scientific knowledge and technical abilities in providing more reliable data on antenatal measurements.Conclusion: Consistent scientific and technical training among midwives is required to update their knowledge and skills, particularly those relating to documenting the results of antenatal examinations at different stages of pregnancy and using that information to assess potential risks and identify necessary interventions. This should also be followed by routine monitoring on the quality of collected antenatal data. This can be one of the enabling actions to achieve the 2030 Sustainable Development Goals target in reducing neonatal mortality in Indonesia.Keywords: scientific and technical training, midwives, routine collection, reliable antenatal data, fetal well-being